IDENTIFICATION OF REPRODUCTIVE DISORDERS IN FEMALE CATTLE AT LOCAL FARMS IN WOHA SUB-DISTRICT, BIMA REGENCY - HY, Lukman; khoirani, kuntum; Karni, Ine (Universitas Syiah Kuala, 2023)
This research aims to identify reproductife disorders in female cattle raised by farmers in Woha Sub-district, Bima Regency, West Nusa Tenggara Province. The study involves the identification of 141 female cattle (56 heifers and 85 cows). The research is carried out by bringing the cattle to the designated locations determined by the farmers group leader, which includes fields and barns. Data collection is conducted through rectal examination of the reproductive system and analysis of records from farmers and officials. The research method includes several stages, namely anamnesis, clinical examination, and rectal examination of the reproductive system. The obtained data is then recorded and analyzed descriptively. Based on the examination results, it is known that 210 female cattle experienced reproductive disorders, including silent heat (4.55%), vaginitis (21.8%), follicular cysts (12.73%), persistent corpus luteum (11.82%), ovarian hypofunction (5.45%), and endometritis (20.91%) of cows and silent heat (8%), vaginitis (28%), follicular cysts (12.73 %) corpus luteum persisten (15 %), and ovarian hypofunction (5%) of heifers.